Variação espaço-temporal e tendências da evapotranspiração de referência no Rio Grande do Sul - Melo, Giane Lavarda (2024)
Reference evapotranspiration (ETo), considered a meteorological element, occurs under standardized conditions and is influenced by meteorological variables specific to each location and period, presenting significant spatiotemporal variability. Accurate ETo estimates are essential for effective water resource management and planning of agricultural activities. The main objective of this work was to analyze the variability of ETo in Rio Grande do Sul (RS), by evaluating trends and clusters, based on a set of daily historical meteorological data between 1990 and 2022. To achieve the main objective, the following specific objectives were outlined: i) to quantify ETo in different regions of RS, representing its trends in annual and seasonal series; and ii) to characterize ETo and the correlations of meteorological variables with ETo through multivariate statistical methods of principal component analysis (PCA) and hierarchical and non-hierarchical clustering (Clusterization). The results obtained demonstrated particularities in the behavior of ETo and the main meteorological variables throughout the RS, indicating, despite the upward trend in maximum relative humidity, the predominance of a more arid climate in the last three decades. This statement is based on the presentation of increasing trends in the meteorological variables, vapor pressure deficit, wind speed and solar radiation, and a decreasing trend in the meteorological variable minimum relative humidity. Despite specific regional particularities, the spatial variability of the accumulated ETo showed an increasing pattern in the East-West direction, evidencing that the climate factors altitude, latitude and continentality/maritimity have a strong influence on the estimation of ETo in RS. Through multivariate statistical analysis, it was possible to verify that the meteorological variables maximum temperature and solar radiation acted directly on the determination of ETo in the seasonal periods spring, summer and autumn. Inversely influencing, the variables maximum and minimum relative humidity were equally important for the determination of ETo, while wind speed presented a third level of importance. Spatially, five distinct regions were demarcated according to the daily estimate of ETo, with maximum rates ranging from 5,0 mm day-1 in summer, 4,6 mm day-1 in spring, 2,4 mm day-1 in autumn and 2,33 mm day-1 in winter. The results obtained demonstrated particularities in the spatial-temporal distribution of ETo and confirm the importance of studies of this thematic nature as a tool to aid agricultural activities, with more accurate water consumption forecasts, in addition to sustainable planning of water resources and guidance of new climate modeling efforts in subtropical regions.